2014
DOI: 10.1177/1091581814537087
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Effect of Aspartame on Ionic Homeostasis and Monoamine Neurotransmitters in the Rat Brain

Abstract: Aspartame is one of the most widely used artificial sweeteners globally. Data concerning acute neurotoxicity of aspartame is controversial, and knowledge on its chronic effect is limited. In the current study, we investigated the chronic effects of aspartame on ionic homeostasis and regional monoamine neurotransmitter concentrations in the brain. Our results showed that aspartame at high dose caused a disturbance in ionic homeostasis and induced apoptosis in the brain. We also investigated the effects of aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 66 publications
0
8
1
Order By: Relevance
“…These results were contrary to those of Abhilash et al (33), who found that other artificial sweeteners as aspartame decreased dopamine in corpus striatum and cerebral cortex, and serotonin in corpus striatum. With respect to 5-HIAA levels, precursor of serotonin, it decreased in striatum and cerebellum/medulla oblongata of animals that received sweeteners and cytarabine alone or combined.…”
Section: Biochemical and Histological Changes Produced By Sweeteners contrasting
confidence: 57%
“…These results were contrary to those of Abhilash et al (33), who found that other artificial sweeteners as aspartame decreased dopamine in corpus striatum and cerebral cortex, and serotonin in corpus striatum. With respect to 5-HIAA levels, precursor of serotonin, it decreased in striatum and cerebellum/medulla oblongata of animals that received sweeteners and cytarabine alone or combined.…”
Section: Biochemical and Histological Changes Produced By Sweeteners contrasting
confidence: 57%
“…Another source of neural effects may be excitotoxicity: Aspartame is metabolized into phenylalanine (50%) and aspartic acid (40%), as well as methanol (10%) . Brain levels of aspartic acid increase acutely after aspartame ingestion .…”
Section: Dietary Triggersmentioning
confidence: 99%
“…Phenylalanine also has the potential to directly interact with NMDARs by competing at the glycine binding site to modulate NMDAR activity [ 38 , 39 ]. Additionally phenylalanine may modulate glutamatergic signaling by altering CNS regional catecholamine levels, for example dopamine [ 40 , 41 ], which can in turn regulate NMDAR surface expression and activity [ 42 ]. Since phenylalanine has the potential to cross both the BBB and the placenta [ 43 ] and to preferentially accumulate in the fetus [ 44 ], this could affect glutamatergic signaling particularly in mice where the activity of phenylalanine hydroxylase, the enzyme necessary to convert phenylalanine to tyrosine, is not active until the last stages of gestation [ 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%